Trends in blood pressure changes and hypertension prevalence in Australian adults before and during the COVID‐19 pandemic - Janis M. Nolde; Fleur Streets; Denny Meyer; Won Sun Chen; Jiajun Wei; Nilmini Wickramasinghe; Patrick Hannebery; Gavin W. Lambert; Markus P. Schlaich (The Journal of Clinical Hypertension, 2024)
Abstract Efforts to limit the impact of the coronavirus disease (COVID‐19) pandemic led to the implementation of public health measures and reallocation of health resources. To investigate trends in blood pressure (BP), hypertension and BMI in the Australian population during the COVID‐19 pandemic, data from publicly accessible health stations were analyzed. Average BP and BMI measured by the SiSU Health Station network in Australia in over 1.6 million health screenings were compared between the years 2018 and 2021. Additionally, paired trajectories for BP and BMI development before and during the COVID‐19 pandemic were calculated. Comparisons between pre‐COVID years and post‐COVID years of 2018 versus 2020, 2019 versus 2020, 2018 versus 2021, and 2019 versus 2021 showed increases in average adjusted systolic BP of 2.0, 1.7, 2.6, and 2.3 mmHg, respectively. Paired analysis of longitudinal data showed an overall increase in the trajectory of systolic BP of 3.2 mmHg between pre‐ and post‐COVID years. The prevalence of hypertension in users of the health stations increased by approximately 25% in the years 2020–2021. Similar trends were seen for BMI. Data from public Australian health stations indicated a strong trend toward higher BP during the COVID‐19 pandemic. At the population level, BP increments have been shown to markedly increase cardiovascular disease risk. Anti‐pandemic measures need to be carefully evaluated in terms of secondary public health effects and health support systems extended to effectively target cardiovascular risk.